KOLABORASI MAHASISWA BERSAMA MASYARAKAT DALAM MENINGKATKAN PEMBANGUNAN PADUKUHAN KEDUNGBUWENG MELALUI KULIAH KERJA NYATA REGULER UNIVERSITAS COKROAMINOTO YOGYAKARTA PERIODE XLIII - Kusumawati, Intan; Pratama, Rikki (Universitas Cokroaminoto Yogyakarta, 2025)
The Real Work Lecture was held in Padukuhan KedungBuweng. For 4 weeks and 3 days starting from 05 February to 06 March 2024. The programs are designed sequentially starting with discussions between KKN groups, community service officials, and local communities, especially those that are in direct contact with the programs being designed. The results achieved from the entire KKN program include developing community skills and helping develop Human Resources (HR) to increase the potential of local villages. In the field of education, namely literacy and learning programs, both academic and religion-based, are implemented to develop quality human resources from an early age. Apart from that, the provision of a reading corner to improve children's literacy at Padukuhan KedungBaweng. In the field of religion, namely the empowerment of mosques and TPAs. In the fields of environment and planning, building road fences and land management, as well as providing land inventory. In the legal field, namely the sticking of anti-bullying posters and the socialization of acts of violence against children. In the economic sector, namely the socialization of the hobby of saving and making a map of MSMEs in Padukuhan KedungBuweng, Wukirsari Village, Kapanewon Imogiri, Bantul Regency, Yogyakarta Special Region Province.